Analysis of the Potential of Wadu Pa'a Cultural Tourism in Kananta Village for the Development of Sports Tourism - Amar, Khairul; Satriawan, Rabwan (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2023)
a cultural tourism attraction, this can be seen from the several heritage buildings of Hindu and Buddhist history and religion which have high historical and cultural values. The most significant cultural tourism objects in Kananta Village are found in Soromandi District, Bima Regency. Wadu pa'a Cultural Tourism can actually be developed into sports tourism because it has great potential as an attraction and a means of regional promotion. People who come to witness an event or championship can also have a tour while people who watch the championship through television viewing will be interested in visiting the area. The purpose of this research is to analyze the potential of wadu pa'a for the development of sports tourism. This study used a qualitative descriptive method through direct observation with research related parties. While the analytical method used is the analysis of Strength, Weakness, Opportunity and Threats (SWOT). Strength, Weakness, Opportunity, and Threat (SWOT) analysis is used to analyze potentials and problems in culture-based tourism and local wisdom at each research location including internal and external potentials and problems. Based on the results of the analysis that wadu pa'a cultural tourism has the potential to be developed into sports tourism.